Strategi Branding dan Digital Marketing dalam Membangun Brand Lokal: Studi Kasus Almaz Fried Chicken - Adi Iryanto; Oskar Judianto (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This study aims to analyze the branding and digital marketing strategies implemented by Almaz Fried Chicken, a local brand, to build awareness and accelerate market expansion in the digital era. The study used a qualitative approach with a case study method, through digital observation, in-depth interviews, and documentation analysis of brand activities on social media. The analysis was conducted thematically to identify marketing strategy patterns that include visual identity, brand narrative, and digital media utilization. The results show that the success of Almaz Fried Chicken is determined not only by product quality, but also by the strength of consistent visual branding and an effective digital communication strategy. A simple, modern, and easily recognizable visual identity plays a crucial role in increasing brand recall, while the narrative as a